ANALYSIS OF THE SOMALI PIRATE ATTACKS IN THE INDIAN OCEAN (2005-2011): EVOLUTION AND MODUS OPERANDI - Ibáñez Gómez, Fernando; Esteban Navarro, Miguel Ángel (Journal of the Spanish Institute for Strategic Studies, 2013)
The aim of this article is to find out about the modus operandi of Somali piracy during its most intensive period of activity: 2005-2011. The method used consists of the identification, matching and analysis of 19 categories for each one of the 1,190 incidents attributed to Somali pirates by diverse sources of official information. The results make it possible to demonstrate a general panorama of the pirate attacks and the way they have evolved, and another more specific one that reflects the diverse parts of the Indian Ocean in which they have taken place. The capability of Somali pirates to adapt in order to continue with their activity in the face of the measures carried out to repress them, and how they have become a threat to international security is highlighted and analysed. It is concluded that the methodology put forward has been useful and it can be used to analyse other modern maritime piracy phenomena and to carry out comparative studies